(untitled) (International Research Journal of Ayurveda & Yoga, 2021)
Background: Gridhrasi is one among the disease, has been described in Ayurvedic classics, under 80 types of Nanatmaja Vata vikaras. Among the Bahya Chikitsa, Agnikarma is commonly practicing procedure in recent trend. The procedure of Agnikarma is very short and gives instant relief. So here Agnikarma is tried with Vishatindukavati also. Here both the treatments are done in the management of Gridhrasi.Objectives of the study: To evaluate the effect of Agnikarma with Vishatinduka vati in Gridhrasi. Materials and Methods: A total of 30 patients were selected from O.P.D and I.P.D of Department of Shalya Tantra, Shri shiva yogeshwar rural Ayurvedic Medical College and Hospital, Inchal. After fulfilling the inclusion and exclusion criteria. The patients are grouped in one group and given Agnikarma along with Vishatinduk Vati orally. Assessment of results was done by considering the baseline data of subjective and objective parameters after treatment. Results: The Percentage of Improvement on Ruk is 47.36%, Toda is 53.70%, Stambha is 46.87 %, Spandana is 48.14%, Aruchi 47.36 %, Gaurav 53.70%, SLR 46.87%, Walking Distance 48.14%. Conclusion: Result is appreciable as Vishatindukadivati has Ampachaka effect due to Maricha and chincha and Agniverdhika having Ushna veerya and Agnikarma pacifies Vata and Kapha and hence relieves the symptoms.